Children of Mentally III Parents at Risk Evaluation (COMPARE): Design and Methods of a Randomized Controlled Multicenter Study—Part I - Christiansen, Hanna; Reck, Corinna; Zietlow, Anna-Lena; Otto, Kathleen; Steinmayr, Ricarda; Wirthwein, Linda; Weigelt, Sarah; Stark, Rudolf; Ebert, David D.; Buntrock, Claudia; Krisam, Johannes; Klose, Christina; et al. (Frontiers in Psychiatry, 2019)
Objectives: Mental disorders are frequent, associated with disability-adjusted life years, societal, and economic costs. Children of parents with a mental illness (COPMI) are at an increased risk to develop disorders themselves. The transgenerational transmission of mental disorders has been conceptualized in a model that takes parental and family factors, the social environment (i.e., school, work, and social support), parent-child-interaction and possible child outcomes into account. The goal of the “Children of Mentally Ill Parents At Risk Evaluation” (COMPARE) study will thus be twofold: (1) to establish the efficacy and cost-effectiveness of a high-quality randomized controlled trial (RCT) with the aim of interrupting the intergenerational transmission of mental disorders in COPMI, (2) to test the components of the trans-generational transmission model of mental disorders. Methods: To implement a randomized controlled trial (RCT: comparison of parental cognitive behavioral therapy/CBT with CBT + Positive Parenting Program) that is flanked by four add-on projects that apply behavioral, psychophysiological, and neuro-imaging methods to examine potential moderators and mediators of risk transmission (projects COMPARE-emotion/-interaction/-work/-school). COMPARE-emotion targets emotion processing and regulation and its impact on the transgenerational disorder transmission; COMPARE-interaction focuses especially on the impact of maternal comorbid diagnoses of depression and anxiety disorders and will concentrate on different pathways of the impact of maternal disorders on socio-emotional and cognitive infant development, such as parent-infant interaction and the infant's stress regulation skills. COMPARE-work analyzes the transmission of strains a person experiences in one area of life to another (i.e., from family to work; spill-over), and how stress and strain are transmitted between individuals (i.e., from parent to child; cross-over). COMPARE-school focuses on the psychosocial adjustment, school performance, and subjective well-being in COPMI compared to an adequate control group of healthy children. Results: This study protocol reports on the interdisciplinary approach of COMPARE testing the model of the transgenerational transmission of mental disorders. Conclusion: The combination of applied basic with clinical research will facilitate the examination of specific risk transmission mechanisms, promotion, dissemination and implementation of results into a highly important but largely neglected field. Clinical Trial Registration: DRKS-ID: DRKS00013516 (German Clinical Trials Register, https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00013516).